Digenic Inheritance of Shortened Repeat Units of the D4Z4 Region and a Loss-of-Function Variant in SMCHD1 in a Family With FSHD - Cascella, Raffaella; Strafella, Claudia; Caputo, Valerio; Galota, Rosaria Maria; Errichiello, Valeria; Scutifero, Marianna; Petillo, Roberta; Marella, Gian Luca; Arcangeli, Mauro; Colantoni, Luca; Zampatti, Stefania; Ricci, Enzo; et al. (Frontiers in Neurology, 2018)
Facioscapulohumeral muscular dystrophy (FSHD) is a neuromuscolar disorder which is typically transmitted by an autosomal dominant pattern, although reduced penetrance and sporadic cases caused by de novo mutations, are often observed. FSHD may be caused by a contraction of a repetitive element, located on chromosome 4 (4q35). This locus is named D4Z4 and consists of 11 to more than 100 repeated units (RU). The D4Z4 is normally hypermethylated and the genes located on this locus are silenced. In case of FSHD the D4Z4 region is characterized by 1-10 repeats and results in the region being hypomethylated. However, 5% of FSHD cases do not carry the short allele of D4Z4 region. To date, two forms of FSHD (FSHD1 and FSHD2) are known. FSHD2 is usually observed in patients without the D4Z4 fragment contraction and carrying variants in SMCHD1 (18p11.32) gene. We report the case of a young adult patient who shows severe symptoms of FSHD. Preliminary genetic analysis did not clarify the phenotype, therefore we decided to study the family members by genetic and epigenetic approaches. The analysis of D4Z4 fragment resulted to be 8 RU in the affected proband and in his father; 26 RU in the mother and 25 RU in the maternal uncle. SMCHD1 analysis revealed a heterozygous variation within the exon 41. The variant was detected in the proband, her mother and the uncle. Furthermore, epigenetic analysis of CpG6 methylation regions showed significant hypomethylation in the affected patient (54%) and in the mother (56%), in contrast to the father (88%) and the uncle (81%) carrying higher methylation levels. The analysis of DR1 methylation levels reported hypomethylation for the proband (19%), the mother (11%) and the uncle (16%). The father showed normal DR1 methylation levels (>30%). Given these results, the combined inheritance of SMCHD1 variant and the short fragment might explain the severe FSHD phenotype displayed by the proband. On this subject, SMCHD1 analysis should be promoted in a larger number of patients, even in presence of D4Z4 contractions, to facilitate the genotype-phenotype correlation as well as, to enable a more precise diagnosis and prognosis of the disease.